OPTIMIZATION OF THE RECIPE COMPOSITION OF CUPCAKES ENRICHED WITH EXTRUDED SUNFLOWER SEED FLOUR (FESSK) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
The actual direction in the production of confectionery products from flour is the use of new types of raw materials to improve the quality and nutritional value of confectionery. The flour product is a cupcake that uses local raw materials helps reduce food waste and stability of the AGRO -FOOD ecosystem. Due to the chemical composition of the seeds of extruded sunflower, sunflower seeds are a unique raw materials ingredient containing polyunsaturated fatty acids and a complex of water and fat-soluble vitamins. It is shown that the introduction of flour from the extruded nucleus of sunflower seeds provides, along with increased nutritional value of the formation of the necessary physico-chemical and structural-rocological properties and allows you to attribute a new product to the category of functional. It is established that with a partial replacement of the PLVG by 5.0%; 10.0%; 15.0% FESSK the output of the finished product increases by 4.7%; 4.9%; 5.0% respectively. What can be explained by FESSK stabilizing and moisture capacity. It is established that a partial replacement of PBVG by 5.0 %; 10.0 %; 15.0 % FESSK improves texture and appearance (shape, surface, breaking) of cupcakes at the expense of water and fat-holding capacity of FESSK. The best organoleptic performance has products when replacing PBVG by 10.0 % beans, that is, when the BPVG ratio: FESSK = 90:10. The rational mass fraction of flour from the extruded nucleus of sunflower seeds was determined - 10.0% of the total weight of flour. This new food product has revealed the advantages of consumption compared to similar products that are already on the market.
Keywords: cupcakes; flour products; flour from extruded sunflower seeds (FESSK); raw materials; nutritional value; recipe; technology; secondary products of the oil industry; system of agro-food products